If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 6) + (5x + 4) = 0 Reorder the terms: (6 + 2x) + (5x + 4) = 0 Remove parenthesis around (6 + 2x) 6 + 2x + (5x + 4) = 0 Reorder the terms: 6 + 2x + (4 + 5x) = 0 Remove parenthesis around (4 + 5x) 6 + 2x + 4 + 5x = 0 Reorder the terms: 6 + 4 + 2x + 5x = 0 Combine like terms: 6 + 4 = 10 10 + 2x + 5x = 0 Combine like terms: 2x + 5x = 7x 10 + 7x = 0 Solving 10 + 7x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 7x = 0 + -10 Combine like terms: 10 + -10 = 0 0 + 7x = 0 + -10 7x = 0 + -10 Combine like terms: 0 + -10 = -10 7x = -10 Divide each side by '7'. x = -1.428571429 Simplifying x = -1.428571429
| 7r^2+20r-3=0 | | 8x+6=7x-9 | | 2x+10=-2-4x | | -6z-11=61 | | 20x-16x-160=30x+360 | | y=108+16(11) | | 2X+457= | | 5*(2x-11+17)=52 | | 50-3x=30 | | log1024/5√3 | | 3p-15+(-3p)=-27 | | (4x+1)(7-3x)=0 | | -y^2+2y+x+2=0 | | (5a+3)=14a-29 | | -0.5x+2y=2 | | (1/3)9cu | | 5/7:15/14=6/5 | | ax-by=2 | | -12X+7X=13 | | -3r*4rx+x+12= | | -5=C-10 | | 15n^2-30n=0 | | 9(t-3)+36t=6(t+2) | | 3-(x-4)=2x+5 | | 12s^3+22s^2-70s=0 | | [10-5(x-2)]=(x+1) | | 5+5w=2+11w | | 6x-3=15-48 | | 3/x=9/2 | | 7/8*h=1/5 | | 35u^2-39u-14=0 | | 10.1+5.3=w |